PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI INTRINSIK, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI MIE GACOAN SOEKARNO HATTA TLOGOSARI, SEMARANG - Ikram, Zul; Mahmud, Nuruddin (Jurnal Manajemen dan Profesional, 2025)
The purpose of this study is to examine how work discipline, intrinsic motivation, and transformational leadership can enhance employee performance in the culinary industry. Using a census sampling technique involving 45 active respondents, the study's population comprised every employee of Mie Gacoann Soekarno Hatta Tlogosari, Semarang. Using the SmartPLS tool, the Partial Least Squares Structural Equation Modeling method was used to analyze the data. The results showed that all three variables partially contributed significantly to employee performance. Transformational leadership has a significant effect on employee performance, intrinsic motivation has a significant effect on employee performance, and work discipline has also been shown to have a significant effect on employee performance. The conclusion of this study confirms that these variables are strategic elements in building superior performance and strengthen the theory of work behavior in the context of modern culinary organizations.